Triglyceride-glucose index is associated with all-cause mortality in critically ill patients with alcohol use disorder: a retrospective cohort study - Yu Pan; Yue-yue Huang; Lian-min Ye; Xiao-hua Zhang; Jing-ye Pan; Yi-hua Dong (BMC, 2024)
Abstract Background The relationship between Triglyceride-glucose (TyG) index and clinical outcomes in patients with alcohol use disorder (AUD) is unclear. The aim of this study was to evaluate the association between TyG index and all-cause mortality in critically ill patients with AUD. Methods We used data from the multi-parameter intelligent monitoring in intensive care IV (MIMIC-IV) database. The patients were equally divided into quartiles. Kaplan-Meier curves were used for survival analysis. The primary endpoint of the study was 28-day mortality, followed by 1-year mortality. We used Cox proportional hazard models to assess the relationship between TyG index and all-cause mortality at different endpoints. Results A total of 537 AUD patients were included. Using TyG value as a continuous variable (HR 1.460, 95% CI 1.121-1.903, p = 0.005) and categorical variable (HR 1.447-3.477 from Q2 to Q4, with Q1 as reference), elevated TyG value was significantly associated with increased 28-day mortality. TyG was positively associated with 1-year mortality in AUD patients with an HR of 1.295 (95% CI 1.011-1.659, p = 0.041). Conclusion TyG index is positively associated with different clinical outcomes of critically ill AUD patients.